If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + 14 = -1x Reorder the terms: 14 + -3x = -1x Solving 14 + -3x = -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 14 + -3x + x = -1x + x Combine like terms: -3x + x = -2x 14 + -2x = -1x + x Combine like terms: -1x + x = 0 14 + -2x = 0 Add '-14' to each side of the equation. 14 + -14 + -2x = 0 + -14 Combine like terms: 14 + -14 = 0 0 + -2x = 0 + -14 -2x = 0 + -14 Combine like terms: 0 + -14 = -14 -2x = -14 Divide each side by '-2'. x = 7 Simplifying x = 7
| 3G-g=18 | | 7y+3y=10 | | 7y+3y=19 | | y=x^2+10x+21 | | 11x-2x=27 | | 10c-8c=10 | | -3x+14=-3 | | 16=q-125 | | 3n^2=-n | | 3+(4+2)5=x | | 2(x+2)-7=3x-17 | | 7x-5x=24-8 | | 3a+(4a+2)5=x | | 3w-4+5w-2= | | x^2+3+7=6x+18 | | -1.7-(-13.4)=x | | 5/6x-9+3-2/3x= | | x+12=46 | | 3x+44-4x=3-5x+5 | | 2(x+1)+(x+3)=3x-13 | | 3+8x=3(2x-11) | | 3-4a=(a-3) | | x+5+x-3+x=x | | x+5+x-3x= | | 7++9= | | -[6z-(8z+1)]=1+(1z+2) | | 2(X-8)=X+17 | | -[6z-(8z+1)]=1t(1z+2) | | (10+1.50)-(6+1)= | | (8+w)(5w+7)=0 | | 8-2x+2=5x+3 | | 8-2x+2=5x |